Assessing the Influence of Investor Confidence on Economic Growth in Nepal: A Comprehensive Non-Granger Analysis (The International Research Journal of Management Science, 2024)
Background: Nepal's economic growth is influenced by its capital market, with the Nepal Stock Exchange Index (NEPSE) and the ratio of market capitalization to paid-up capital (RMP) serving as indicators of investor confidence. Understanding how these indicators relate to GDP can clarify the stock market's role in shaping economic policies and investments.Objectives: The study aims to assess causal relationships between GDP, NEPSE, and RMP in Nepal. It examines whether stock market performance predicts GDP changes and the extent of any feedback effect from GDP.Method: Using annual data and the Toda-Yamamoto Granger non-causality test, the study examines interactions between GDP, NEPSE, and RMP without requiring adjustments for stationarity. The model tests for unidirectional or bidirectional causality among these variables.Results: The results reveal a unidirectional causality from NEPSE to GDP, suggesting that stock market performance impacts economic growth in Nepal. Both NEPSE and RMP show predictive power over GDP, while GDP’s feedback effect on these indicators is weak.Conclusion: The study concludes that Nepal’s stock market significantly influences economic growth, with NEPSE and RMP acting as leading indicators of GDP.Implications: The findings suggest that the policymakers should prioritize market stability and accessibility to support economic growth. Enhanced regulation, transparency, and broader market participation could strengthen investor confidence and positively impact Nepal's economic trajectory.